IMPLEMENTATION OF SCRAMBLE METHOD FOR LEARNING “CLOCK” IN ENGLISH LEARNERS CLASS V SDN PERUMNAS 1 CIBODAS - Mikala, Ikrima Gina; Ramadhiyanti, Ananda; Sudarmaji, Imam (PROGRES PENDIDIKAN, 2025)
A teacher could utilize certain methods at all levels for teaching a language. An effective teaching technique will immediately contribute to interest learners in the learning process and boost students' motivation and achievement in learning English. This research is done by mixing methods which are qualitative and quantitative (quasi experimental method). It is a scramble letter game, which is a way to develop words through cooperative and competitive activity. As a result, the researcher wants to know if the scramble letter game increases student achievement in English. The research results indicate the effectiveness of applying a scramble letter game while teaching English has increased in the experiment class with an average score of 30-80, but not in the control class with an average score of 70. Applying the scramble letter game as a technique while teaching English at SDN Perumnas 1 Cibodas in the Academic Year 2022/2023 is quite helpful. Based on the findings, it is advised that the scramble letter game be employed as an alternative and variation of their teaching and learning strategies.